Exploring the Causality Between Hypothyroidism and Non-alcoholic Fatty Liver: A Mendelian Randomization Study - Qiu, Shizheng; Cao, Peigang; Guo, Yu; Lu, Haoyu; Hu, Yang (Frontiers in Cell and Developmental Biology, 2021)
The etiology of nonalcoholic fatty liver disease (NAFLD) involves complex interaction of genetic and environmental factors. A large number of observational studies have shown that hypothyroidism contributes to a high risk of NAFLD. However, the exact causality is still unknown. As Mendelian randomization (MR) was proposed, it is possible to explore the causality between the two diseases. In this study, in order to explore the influence of intermediate phenotypes on outcome, 9 independent SNPs of hypothyroidism obtained from the genome-wide association study (GWAS) were used as instrumental variables (IVs) to perform MR analysis on NAFLD. Since there was no heterogeneity between IVs (P=0.70), a fixed effect model was used. The correlation between hypothyroidism and NAFLD was evaluated by using Inverse variance weighted method (IVW) and Weighted median method. Then the sensitivity test was analyzed. Results showed that there was a high OR (1.7578; 95%CI [1.1897 to 2.5970]; P = 0.0046) and low intercept (-0.095; P=0.431). None of the SNPs drove the overall result (P < 0.01). Simply, we proved that the risk of NAFLD increases significantly on patients with hypothyroidism. Furthermore, we explained possible causes of NAFLD caused by hypothyroidism.